Humoral Immune Response to Newcastle Disease Vaccine (Lastoa Strain) in Broilers - Shuaib, Muhammad; Khan, Hamayun; Sajid-ur-Rehman; Ashfaque, Muhammad (International Journal of Poultry Science, 2006)
This research was carried out at the Department of Microbiology, University of Agriculture Faisalabad, Pakistan in order to study humoral immune response to Newcastle disease vaccine (Lastoa strain) in broilers. For this purpose, 30-day-old broiler chicks were procured from Olympia chicks. The chicks were divided into three groups containing 10 chicks each. The HI-Ab-titre against ND virus in the control group showed an overall Ab-titre with GMT=3.99.The HI-Ab-response in broilers chicks with single dose of Lastoa vaccine ranged from 1:8 to 1:32.This group showed an overall HI-Ab- titer with GMT=13.931. While the HI-Ab titer against ND virus was found to be in the range of 1:16 to 1:128 in broilers chicks which were vaccinated with the 1st dose of ND virus (LaSota strain) at the age of 2 weeks followed by a booster dose with the same strain at 3 weeks of age. The overall HI-Ab-titre against LaSota strain of ND virus came out to be GMT=55.692. During present investigation a significant increase in HI-Ab-titre (GMT) against ND virus was observed in broilers from single to boostered vaccination group.